Comparative Chloroplast Genomics of Corydalis Species (Papaveraceae): Evolutionary Perspectives on Their Unusual Large Scale Rearrangements - Xu, Xiaodong; Wang, Dong (Frontiers in Plant Science, 2021)
The chloroplast genome (plastome) of photosynthetic angiosperm is generally highly conserved, although unusual phenomenon of large scale rearrangements has also been reported in a few linages. In the present study, we revealed Corydalis to be another extraordinary linage with extensive large scale plastome rearrangements. The pattern, origin, evolution, and phylogenetic utility of those rearrangements were explored and discussed. The four newly assembled Corydalis plastomes shared typical angiosperm quadripartite structure, but exhibited abnormal IR, SSC, and total genome size. In addition, we detected unusual rearrangements within each part. They are: (1) Two parallel relocations of the same five genes (trnV-UAC–rbcL) from the typically posterior part of LSC region to the front, either downstream of atpH gene (C. saxicola) or trnK-UUU gene (C. davidii and C. hsiaowutaishanensis), and unique relocation of rps16 gene from LSC region to IR region (C. adunca). The three relocation events occurred independently after the diversification of those linages, and were possibly specific to and diagnostic for the three Corydalis subgenera (Sophorocapnos, Corydalis, and Cremnocapnos, respectively). (2) Uniform inversion of an 11–14 kb segment (ndhB–trnR-ACG) in the IR region in all the four Corydalis plastomes. (3) Unconventional large scale expansions (> 10 kb) of IR into the SSC region, and correspondingly extremely diminished SSC regions. (4) Extensive pseudogenization or loss of 13 genes (accD, clpP, and 11 ndh genes) in one or more Corydalis plastomes. Phylogenetic analyses (MP, ML, and BI) based on complete plastomes resolved all the Corydalis branches with full support, and revealed a different section arrangement which contradict with the arrangement deduced from morphological characters to some extent. This indicated that some of the morphological characters that were once widely used for taxonomic and systematic considerations were possibly results of parallel, or convergent evolution. A plastome-wide survey for highly informative phylogenetic markers revealed previously unused regions for future Sanger-based studies. This study provided insights into the evolution of plastomes throughout the three Corydalis subgenera, and served as the first step towards understanding the taxonomy, phylogeny, and evolution of Corydalis in a genomic perspective.